NILAI-NILAI EDUKASI DALAM NOVEL SRIMENANTI KARYA JOKO PINURBO - Ponco Prastio; Martono Martono; Sesilia Seli (Universitas Tanjungpura, 2023)
This study aims to describe the results of an analysis of the educational value contained in the novel which includes social values and individual character values in Joko Pinurbo's Srimenanti novel. The research method used in this study is a descriptive method with a qualitative research form. The approach used in this study is the sociology of literature approach, especially the sociology of works. Sources of data in this study, is a documents in the form of a novel. The novel used in this study is the novel Srimenanti by Joko Pinurbo. The technique used in this study is a documentary study namely a documents in the form of a novel. The tools used in this study were stationery and laptops. The results of this study indicate that the educational value in Joko Pinurbo's Srimenanti novel associated with, namely social values and individual character values. Social values include, the value of affection, the value of helping, the value of caring, the value of politeness, and the value of courage. Individual character values include honesty values, religious values, and independence values. Researchers have designed lesson plans that utilize Joko Pinurbo's Srimenanti novel as learning material, specifically to achieve KD 3.9 and 4.9 for class XII SMA students